Nanocompósito de polpa de mamão e nanopartículas de quitosana para aplicação em embalagens - Lorevice, Marcos V.; Moura, Marcia R. De [UNESP]; Mattoso, Luiz H. C. (Sociedade Brasileira de Química, 2014)
Nanocomposite materials have been incorporated into biopolymers, (e.g. hydroxypropyl methylcellulose), to improve their physical and chemical properties and enable them to be applied in food packaging, especially for their biodegradable and renewable properties. With this addition, fruit puree has been incorporated into the films to confer nutritional properties besides color and flavor. Chitosan is of interest in the packaging field since it is a biodegradable, bioabsorbable, antimicrobial agent. Furthermore, chitosan nanoparticles have been widely explored for their interesting properties and potential applications in food packaging. This work was divided into two stages: (1) chitosan nanoparticle synthesis; (2) addition of nanoparticles into HPMC and papaya puree films. Addition of chitosan nanoparticles to HPMC and papaya puree films improved film properties: mechanical, thermal and water vapor barrier. We have developed a novel nanomaterial with great potential for application in packaging to prolong the shelf life of food.
Nanocomposite of papaya puree and chitosan nanoparticles for application in packaging
Keywords: nanoparticles; edible films; papaya puree